Nanoparticles: In Situ Synchrotron X‐Ray Techniques for Real‐Time Probing of Colloidal Nanoparticle Synthesis (Part. Part. Syst. Charact. 5/2013). (28th May 2013) - Sun, Yugang; Ren, Yang
<x xml:space="preserve">Abstract</x> Probing the synthesis of colloidal nanoparticle by in situ synchrotron X‐ray techniques is described by Yugang Sun and Yang Ren on page 399. The article reviews a number of X‐ray techniques emerged in the recent years for realtime probing nanoparticle synthesis in solutionphase reactions, for instance, the time‐resolved high‐energy synchrotron X‐ray diffraction (inset) used for monitoring the formation of colloidal silver nanocubes (image). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>